دور قرار الشراء الاندفاعي في التأثير على الصورة الذهنية لدى المستهلكين "دراسة مسحية على مستهلكي سلع التسوق في محافظة اللاذقية" - نصور ريزان; زيدان عمار (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت هذه الدراسة إلى تحديد مفهوم قرار الشراء الاندفاعي وأهميته والتعريف بمفهوم الصورة الذهنية، كما تهدف الى تحليل تأثير قرار الشراء الاندفاعي على الصورة الذهنية لدى المستهلكين. ولتحقيق ذلك قام الباحث بتحديد ودراسة دور قرار الشراء الاندفاعي في التأثير على الصورة الذهنية لدى المستهلكين وذلك من خلال اجراء دراسة مسحية على مستهلكي سلع التسوق في محافظة اللاذقية، وتضمن مجتمع الدراسة على المستهلكين الذين قاموا بعملية شراء سلع تسوق في الساحل السوري، ومن خلال الاعتماد على دراسة مسحية لمستهلكي سلع التسوق في محافظة اللاذقية وتوزيع 288 استبانة على مستهلكي سلع التسوق فيها، توصلت الدراسة إلى مجموعة من النتائج كان من أهمها: ·توجد علاقة ذات دلالة بين العوامل المؤثرة على قرار الشراء الاندفاعي والصورة الذهنية للمستهلك وفقاً للبعد المعرفي. ·توجد علاقة ذات دلالة بين العوامل المؤثرة على قرار الشراء الاندفاعي والصورة الذهنية للمستهلك وفقاً للبعد السلوكي. ·توجد علاقة ذات دلالة بين العوامل المؤثرة على قرار الشراء الاندفاعي والصورة الذهنية للمستهلك وفقاً للبعد الوجداني. كما قدّم الباحث من خلال هذه الدراسة مجموعة من المقترحات والتوصيات التي من المتوقع أن تساعد أصحاب العلامات التجارية على تعزيز ولاء العملاء بعلامتهم التجارية وبناء اتجاهات إيجابية نحوها عبر مواقع التواصل الاجتماعي. The aim of this study is to identify the impulse buying decision and its importance and to introduce the concept of mental image. It also aims to analyze the effect of the impulse buying decision on the mental image of consumers. In order to achieve this, the researcher identified and studied the role of the purchasing decision in the impact on the mental image of consumers by conducting a survey of consumers of shopping goods in the province of Latakia, and included the study community to consumers who have made the purchase of shopping goods in the Syrian coast, A survey of consumers of shopping goods in Lattakia governorate and the distribution of 288 questionnaires to consumers of shopping goods, the study reached a number of results, the most important of which were: There is a significant relationship between the factors influencing the impulse purchasing decision and the mental image of the consumer according to the cognitive dimension. - There is a significant relationship between the factors affecting the purchase decision impulse and mental image of the consumer according to the behavioral dimension. - There is a significant relationship between the factors affecting the purchase decision impulse and mental image of the consumer according to the emotional dimension. The researcher also presented a set of proposals and recommendations that are expected to help brand owners to promote customer loyalty and build positive attitudes towards them through social networking sites.